Autophagy activation, not peroxisome proliferator‐activated receptor γ coactivator 1α, may mediate exercise‐induced improvements in glucose handling during diet‐induced obesity. Issue 9 (22nd July 2017) - Rosa‐Caldwell, Megan E.; Brown, Jacob L.; Lee, David E.; Blackwell, Thomas A.; Turner, Kyle W.; Brown, Lemuel A.; Perry, Richard A.; Haynie, Wesley S.; Washington, Tyrone A.; Greene, Nicholas P.
Abstract : New Findings: What is the central question of this study? What are the individual and combined effects of muscle‐specific peroxisome proliferator‐activated receptor γ coactivator 1α (PGC‐1α) overexpression and physical activity during high‐fat feeding on glucose and exercise tolerance? What is the main finding and its importance? Our main finding is that muscle‐specific PGC‐1α overexpression provides no protection against lipid‐overload pathologies nor does it enhance exercise adaptations. Instead, physical activity, regardless of PGC‐1α content, protects against high‐fat diet‐induced detriments. Activation of muscle autophagy was correlated with exercise protection, suggesting that autophagy might be a mediating factor for exercise‐induced protection from lipid overload. The prevalence of glucose intolerance is alarmingly high. Efforts to promote mitochondrial biogenesis through peroxisome proliferator‐activated receptor γ coactivator 1α (PGC‐1α) to mitigate glucose intolerance have been controversial. However, physical activity remains a primary means to alleviate the condition. The aim of this study was to determine the combined effects of muscle‐specific overexpression of PGC‐1α and physical activity on glucose handling during diet‐induced obesity. Wild‐type (WT, ∼20) and PGC‐1α muscle transgenic (MCK‐PGC‐1α, ∼20) mice were given a Western diet (WD) at 8 weeks age and allowed to consume food ab libitum throughout the study. At 12 weeks of age, all animals were divided into sedentary (SED) or voluntary wheel running (VWR) interventions. At 7, 11 and 15 weeks of age, animals underwent glucose tolerance tests (GTT) and graded exercise tests (GXT). At 16 weeks of age, tissues were collected. At 11 weeks, the MCK‐PGC‐1α animals had 50% greater glucose tolerance integrated area under the curve compared with WT. However, at 15 weeks, SED animals also had greater GTT integrated area under the curve compared with VWR, regardless of genotype; furthermore, SED animals demonstrated reduced exercise capacity compared with earlier time points, which was not seen in VWR animals. Voluntary distance run per day was correlated with GTT in VWR‐WT, but not VWR‐MCK‐PGC‐1α mice. Voluntary wheel running and genotype independently resulted in a greater LC3II/LC3I ratio, suggesting enhanced autophagosome formation, which was correlated with exercise‐induced improvements in GTT. In conclusion, artificially increasing mitochondrial content does not protect from lipid‐induced pathologies nor does it augment exercise adaptations. Physical activity ameliorates the effects of lipid overload‐induced glucose intolerance, an effect that appears to be related to enhanced activation of autophagy. Abstract :